Revisores (Revista Tempo e Argumento, 2009)
Augusto da Silva, Universidade Federal de SergipeDorval do Nascimento, Universidade do Extremo Sul CatarinenseEnrique Serra Padrós, Universidade Federal do Rio Grande do SulIvonete Pereira, Universidade Estadual do Oeste do ParanáLucília de Almeida Neves Delgado, Universidade de São PauloPaulo Rogério Melo de Oliveira, Universidade do Sul de Santa CatarinaRaimundo Pereira Alencar Arrais, Universidade Federal do Rio Grande do NorteReinaldo Lindolfo Lohn, Universidade do Estado de Santa CatarinaSilvia Maria Fávero Arend, Universidade do Estado de Santa CatarinaZita Rosane Possamai, Universidade Federal do Rio Grande do Sul